PARTISIPASI MASYARAKAT DALAM PEMANFAATAN DANA DESA UNTUK MENUNJANG PENYELENGGARAAN PENDIDIKAN PAUD DESA NANGA KANTUK - Rischa Sindhy Tama; Yohanes Bahari; Riama Al Hidayah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe purpose of This Study is to determine The participation of the community in the utilization of village funds to support the implementation of early childhood education in the village of Nanga Kantuk. A common problem in this research is how the participation of the community in the utilization of village funds support early childhood education in the village of Nanga Kantuk?. The approach used is a qualitative approach with the method of in-depth interviews. Data collection techniques used interviews and documentation. The results of this study showed that community participation in planning, implementation, and supervision of the utilization of village funds to support the implementation of early childhood education in the village of Nanga Kantuk had done well. This is evidenced in the planning stage, that the village government and the community actively follow the village's deliberations. At the stage of implementation, the community formed a team to implement the construction of the education can run well. On the stage of the surveillance, society and the village government is also actively involved in supervising the construction of early childhood education’s building.Keywords: The Participation of the Community, Village Funds, Implementation of the Early Childhood Education